Growth Performances and Carcass of KUB Chicken Fed on A Diet Containing Different Levels of Fermented Mixture of Rice Bran and Protein from Slaughtered House - Ade Akmaludin; Asnawi; Vebera Maslami; I Ketut Gede Wiryawan (Jurnal Biologi Tropis, 2023)
Rice bran is a common poultry feed ingredients. However, its use is limited due to its high fiber content and low phosphorus content. This study aimed to evaluate the effects of feeding a fermented mixture of rice bran and PSW (RPSW) on the growth performances and carcass of KUB chicken. A mixture of two parts of rice bran and one part of PSH was fermented using rumen liquor for 5 days. Two hundred two-week-old KUB chickens were randomly allocated into four dietary treatments with different levels of fermented RPSW i.e.; 0, 10, 20, and 30% for treatments 1, 2, 3, and 4 respectively. Feed was provided ad libitum for ten-week observation period, and drinking water was always available. At the end of the feeding trial, chickens were slaughtered to measure carcasses and their components. The results showed that there were no significant differences in feed consumption and carcass percentage between treatments, but the final body weight, body weight gain, carcass weight, and organ weight of chickens fed rations containing 20 and 30% fermented RPSH were lower than those fed rations containing 20 and 30% fermented RPSH. 30% fermented RPSH. The control or ration was fed a ration containing 10% fermented RPSH. The results indicate that a fermented blend of rice bran and protein from slaughtered house waste incubated with rumen liquor for 5 days can be included in the KUB chicken diet up to 10%.